Scalar-multi-tensorial equivalence for higher order f (R,del R-mu,del(mu 1)del R-mu 2, ... ,del(mu 1) ... del R-mu n) theories of gravity - Cuzinatto, R. R.; Melo, C. A. M. de [UNESP]; Medeiros, L. G. [UNESP]; Pompeia, P. J. (Amer Physical Soc, 2016)
The equivalence between theories depending on the derivatives of R, i.e. f(R, del R, ... ,del R-n), and scalar-multi-tensorial theories is verified. The analysis is done in both metric and Palatini formalisms. It is shown that f(R,del R, ... ,del R-n) theories are equivalent to scalar-multi-tensorial ones resembling Brans-Dicke theories with kinetic terms omega(0) = 0 and omega(0) = -3/2 for metric and Palatini formalisms respectively. This result is analogous to what happens for f(R) theories. It is worth emphasizing that the scalar-multi-tensorial theories obtained here differ from Brans-Dicke ones due to the presence of multiple tensorial fields absent in the last. Furthermore, sufficient conditions are established for f(R,del R, ..., del R-n) theories to be written as scalar-multi-tensorial theories. Finally, some examples are studied and the comparison of f(R,del R, ..., del R-n) theories to f(R,square R,...,square R-n) theories is performed.